Factors Affecting Mortality during Treatment in Pulmonary Tuberculosis Patients, Surin Province, between 2018–2022 - Sanmai, Sattawat; Jirapornkul, Chananya; Yueayai, Khanuengnij; Tantivatananon, Wassana; Rueasao, Chawiwan (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
The study was a retrospective cohort analysis. The objectives of the study were to determine the mortality rate and to identify factors associated with death among pulmonary tuberculosis (TB) patients undergoing treatment in Surin Province, Thailand. Data on pulmonary TB patients were obtained from the National Tuberculosis Information Program (NTIP) database for individuals who were registered and initiated treatment between January 1, 2018, and December 31, 2022. A total of 6,760 pulmonary TB patients were included. Data were analyzed using descriptive statistics, including frequency and percentage, and inferential statistics. The mortality rate among pulmonary TB patients was calculated. Bivariate analysis was conducted to assess associations between individual variables. Multivariate analysis was performed using a generalized linear model (GLMs) with backward elimination to control for confounding factors. The results revealed that 562 patients died, corresponding to a mortality rate of 8.11 per 100,000 population (95%CI:7.46–8.81). Factors significantly associated with mortality included age 58–69 years (adjusted RR = 2.10, 95%CI: 1.56–2.83), age ≥ 70 years (adjusted RR = 4.08, 95%CI: 3.07–5.42), chronic kidney disease (adjusted RR = 1.80, 95%CI: 1.27–2.55), HIV co-infection (adjusted RR = 4.33, 95%CI: 3.17–5.92), chronic alcohol use (adjusted RR = 2.85, 95%CI: 1.89–5.92), and malnutrition (adjusted RR = 2.82, 95%CI: 1.53–5.19). Therefore, healthcare facilities should strengthen care plans for pulmonary tuberculosis patients, particularly for elderly individuals, those with comorbidities such as chronic kidney disease and HIV co-infection, and patients with immunocompromised conditions. Treatment protocols should be appropriately adjusted, with close monitoring of patient symptoms, to help reduce mortality rates among pulmonary tuberculosis patients.